Axiological Foundations for Legal Discourse: Axioms of Law - I. V. Palashevskaya (Научный диалог, 2017)
The article is devoted to the axioms of law as a value-regulatory foundations for legal discourse, explaining the choice of actions and directing the development of the communicative events in the institutional environment. Axiomatics of legal discourse and its types today attracts a wide range of researchers. This is due to the idea that values are the binder component of any institutional community, and the fact that legal discursive practices and their types are a way of approval and constant reproduction of value meanings, which mediate society’s attitude to the law and its representatives. The author shows that the axioms of law are function in the form of concise, stylistically organized, aphoristically compressed utterances, that is, ready-made formulas-symbols of institutional culture. Linguistically-relevant constitutive signs of the axioms of law (precedent, prescriptively, generality, aphoristic brevity, etc.), their specific functions (cumulative, regulatory, informative and symbolic) as the precedent texts of the institutional culture are distinguished. The typological and communicative characteristics of the units in a pragmatic aspect, methods of text-construction as imperative statements are described. The impact of these value phenomena on forming the scripts of institutional interaction, on mental models of appropriate participation in the discourse, on the inner workings of institutional life and its speech and action manifestation is analyzed. Attention is paid to value transformations at the level of informal axiomatic formation of institutional culture.